1996
DOI: 10.1002/(sici)1097-0142(19960101)77:1<172::aid-cncr28>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated thyroid cancer: Impact of adjuvant external radiotherapy in patients with perithyroidal tumor infiltration (stage pT4)

Abstract: In addition to total thyroidectomy, treatment with radioiodine, and TSH-suppressive therapy with thyroid hormone, adjuvant external radiotherapy improves the recurrence-free survival in patients older than age 40 years with invasive PTC and lymph node involvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
92
4
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 200 publications
(103 citation statements)
references
References 27 publications
4
92
4
3
Order By: Relevance
“…In 1996, however, a further retrospective analysis was published containing 99 irradiated and 70 non-irradiated patients with stage pT4, pN0-1 tumors diagnosed according to uniform criteria (i. e. UICC 1987). This study showed a statistically significant survival advantage for irradiated patients over 40 years of age with papillary carcinoma and lymph node involvement [7]. In our study patients with pT4 tumors showed a trend towards better survival (87% vs 46%) with postoperative irradiation than without; this did not reach statistical significance (p = 0.06).…”
Section: External Radiotherapy: Pro and Contracontrasting
confidence: 70%
See 1 more Smart Citation
“…In 1996, however, a further retrospective analysis was published containing 99 irradiated and 70 non-irradiated patients with stage pT4, pN0-1 tumors diagnosed according to uniform criteria (i. e. UICC 1987). This study showed a statistically significant survival advantage for irradiated patients over 40 years of age with papillary carcinoma and lymph node involvement [7]. In our study patients with pT4 tumors showed a trend towards better survival (87% vs 46%) with postoperative irradiation than without; this did not reach statistical significance (p = 0.06).…”
Section: External Radiotherapy: Pro and Contracontrasting
confidence: 70%
“…This is in accordance with the data of the present study, with 10-year survival rates of 92%. These high survival rates involve a further problem: Even though the frequency of local recurrence can be decreased by irradiation [7,20,30], this does not necessarily translate into a significant further prolongation of survival.…”
Section: External Radiotherapy: Pro and Contramentioning
confidence: 99%
“…External radiotherapy is effective in local disease control and prevention of locoregional recurrence for patients with papillary carcinoma. [25][26][27] We have previously shown that external radiotherapy achieves local control in 81% of patients when residual microscopic disease is present and achieves complete regression in 37% of patients with macroscopic disease. 27 Radiotherapy also is effective in the palliation of patients with distressing local symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The standard treatment for locally advanced DTC is surgical resection, radioiodine therapy, and suppression of thyroid-stimulating hormone (TSH) [10,15]. In some retrospective analyses, additional adjuvant radiotherapy was associated with improved local control or survival in these patients [7,12,27]. There has been no randomized trial so far that tested the use of radiotherapy in DTC.…”
Section: Introductionmentioning
confidence: 99%